STRATEGI PENGEMBANGAN COMMUNITY BASED TOURISM SEBAGAI UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT DI KULON PROGO - Sugi Rahayu; Utami Dewi; Kurnia Nur Fitriana (NATAPRAJA, 2016)
This article aims to describe the development of CBT in Kulon Progo and obstacles faced. The method used descriptive qualitative design with Research and Development (R and D) from Borg and Gall (1998). The technique of collecting data used interviews, observation, documentation and Focus Group Discussion (FGD). Data were analyzed using interactive analysis Miles and Huberman. The study found that some strategies may be taken in the development of CBT: to see, to do, to buy, to share, to empower and to sustain of all agriculture, economics and social-cultural potentials in Kulon Progo. Moreover, in implementing CBT, there are steps should be considered as follows: understanding all potentials and resources, establishing CBT’s management, and integrating roles of all stakeholders. However, there are several hindrances in the implementation model that needs to be taken by the manager of CBT in Kulon Progo are: 1). Un-sufficient budget; 2) the lack of human resources; 3) un-readiness of community in viewing the importance of tourism management; 4) the lack of support from private sectors; 5) lack of infrastructure.Keywords: CBT, Strategy, and Empowerment